Acquired Resistance Mechanisms to PD-L1 Blockade in a Patient With Microsatellite Instability-High Extrahepatic Cholangiocarcinoma. (23rd March 2022) - Niger, Monica; Nichetti, Federico; Dell'Angelo, Francesca; Cappelletti, Vera; Pircher, Chiara; Vismara, Marta; Cotsoglou, Christian; Bhoori, Sherrie; Vingiani, Andrea; Di Bartolomeo, Maria; Pietrantonio, Filippo; de Braud, Filippo; et al.
Abstract :